2009
DOI: 10.1248/bpb.32.988
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Down-Regulates Inducible Nitric Oxide Synthase by Inducing Proteasomal Degradation

Abstract: Rapamycin, a macrolide antibiotic, has a potent anti-proliferative effect in multiple cell types and is currently used in kidney transplantation as a clinical immunosuppressant. 1)Rapamycin interacts with FK506-binding protein (12 kDa, FKBP12), and this complex inhibits the mammalian target of rapamycin (mTOR). Recent findings revealed that mTOR controls a diverse set of downstream effectors, some of which are important for cell growth, such as p70 S6 kinase and eukaryotic translation initiation factor 4E-bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 31 publications
2
22
0
Order By: Relevance
“…That result was unexpected, given that PI(3)K is essential for the long-term commitment to aerobic glycolysis in response to stimulation via TLRs 4 , an observation consistent with the known relationship of PI(3)K and Akt. We reason that this inconsistency reflects the fact that signaling via PI(3)K through mTORC1 is essential for promoting iNOS expression and NO production 42,43 , which forces inflammatory DCs to commit to glycolysis in the later stages of their activation 6 . In addition, such long-term commitment to glycolysis would be further supported by mTORC1, through the induction of HIF-1α 5 .…”
Section: Discussionmentioning
confidence: 99%
“…That result was unexpected, given that PI(3)K is essential for the long-term commitment to aerobic glycolysis in response to stimulation via TLRs 4 , an observation consistent with the known relationship of PI(3)K and Akt. We reason that this inconsistency reflects the fact that signaling via PI(3)K through mTORC1 is essential for promoting iNOS expression and NO production 42,43 , which forces inflammatory DCs to commit to glycolysis in the later stages of their activation 6 . In addition, such long-term commitment to glycolysis would be further supported by mTORC1, through the induction of HIF-1α 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al (2000) found that some proteasome mutants are hypersensitive to rapamycin. Furthermore, rapamycin addition promotes proteasome activation, while proteasome inhibition decreases TOR function in mammalian cells (Jin et al 2009;Ko et al 2011). These results provide strong evidence of crosstalk between the ubiquitin-proteasome and TOR1 pathways, and that TOR1 activity inversely correlates with proteasome function under some conditions.…”
Section: Discussionmentioning
confidence: 99%
“…ulating protein translation, the activity of mTOR may also regulate iNOS expression through effects on protein stability (68). The specific post-transcriptional processes modulated by NO that augment iNOS protein levels require further study.…”
Section: Discussionmentioning
confidence: 99%